Burden of epilepsy in rural Kenya measured in disability-adjusted life years. - Ibinda, F; Wagner, R; Bertram, M; Ngugi, A; Bauni, E; Vos, T; Sander, J; Newton, C (2014)
OBJECTIVES: The burden of epilepsy, in terms of both morbidity and mortality, is likely to vary depending on the etiology (primary [genetic/unknown] vs. secondary [structural/metabolic]) and with the use of antiepileptic drugs (AEDs). We estimated the disability-adjusted life years (DALYs) and modeled the remission rates of active convulsive epilepsy (ACE) using epidemiologic data collected over the last decade in rural Kilifi, Kenya. METHODS: We used measures of prevalence, incidence, and mortality to model the remission of epilepsy using disease-modeling software (DisMod II). DALYs were calculated as the sum of Years Lost to Disability (YLD) and Years of Life Lost (YLL) due to premature death using the prevalence approach, with disability weights (DWs) from the 2010 Global Burden of Disease (GBD) study. DALYs were calculated with R statistical software with the associated uncertainty intervals (UIs) computed by bootstrapping. RESULTS: A total of 1,005 (95% UI 797-1,213) DALYs were lost to ACE, which is 433 (95% UI 393-469) DALYs lost per 100,000 people. Twenty-six percent (113/100,000/year, 95% UI 106-117) of the DALYs were due to YLD and 74% (320/100,000/year, 95% UI 248-416) to YLL. Primary epilepsy accounted for fewer DALYs than secondary epilepsy (98 vs. 334 DALYs per 100,000 people). Those taking AEDs contributed fewer DALYs than those not taking AEDs (167 vs. 266 DALYs per 100,000 people). The proportion of people with ACE in remission per year was estimated at 11.0% in males and 12.0% in females, with highest rates in the 0-5 year age group. SIGNIFICANCE: The DALYs for ACE are high in rural Kenya, but less than the estimates of 2010 GBD study. Three-fourths of DALYs resulted from secondary epilepsy. Use of AEDs was associated with 40% reduction of DALYs. Improving adherence to AEDs may reduce the burden of epilepsy in this area.